Learning Motivation: Based on Gender and Academic Abilities - Yusnaeni Yusnaeni; Sudirman Sudirman (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2019)
Student learning outcomes are influenced by several factors. One of them is learning motivation. This research is a descriptive and correlation study that aims to describe and analyze students' learning motivation based on gender and academic ability. The sample of this study was grade 10th students of senior high school in Kupang City, namely: SMAN 5, SMAN 4, and SMAN 1. The determination of school samples and class samples is done by random sampling. The research instrument used the MSLQ motivation questionnaire that was developed and validated by Duncan and McKeachie (2005), while the data of learning outcomes obtained from summative test scores . The results obtained that the average motivation (intrinsic and extrinsic) of students: 1) women are higher than male students, and 2) academic ability is higher than students with lower academic ability, and 3) Extrinsic motivation has a very significant correlation with intrinsic motivation and results learning, for gender and academic ability.The results of this study indicate that an appropriate learning strategy is needed in order to minimize gender differences and academic ability to foster student learning motivation which ultimately impacts on learning outcomes. Keywords: Learning motivation; academic ability; gender; students.